ANALYSIS OF IMPLEMENTATION CONTEXT AND IMPACT OF MANDALIKA SPECIAL ECONOMIC ZONE POLICY ON COMMUNITY EMPOWERMENT THROUGH NON-FORMAL EDUCATION PROGRAMS IN THE TOURISM SECTOR - Raziqin, Khairur; Suryono, Agus; Domai, Tjahjanulin (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study aims to explore the objectives of the Mandalika Special Economic Zone (SEZ), which not only focuses on the development of the tourism sector but also on the enhancement of Human Resources (HR) through non-formal education. The method used is qualitative descriptive employing the Miles and Huberman analysis technique, which includes data reduction, data display, and conclusion drawing. Data consist of primary and secondary data collected through interviews, documentation, and observation. The results show that despite numerous training sessions, their impact on HR development and economic growth in Central Lombok Regency is not significant yet. In-depth evaluation and closer collaboration between the government, ITDC, and the local community are needed to enhance the effectiveness of training programs in the future.